2020
DOI: 10.3390/vetsci7020037
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Sebaceous Adenitis and Concurrent Meibomian Gland Dysfunction in a Dog

Abstract: Sebaceous adenitis and concurrent meibomian gland dysfunction (MGD) were diagnosed in a two-year-old mongrel dog presenting with hypotrichosis, exfoliative dermatitis and blepharitis. Diagnosis of sebaceous adenitis was based on history, clinical signs, the histological demonstration of multifocal lymphohistiocytic and neutrophilic inflammation targeting the sebaceous glands and sebaceous glands loss. MGD was diagnosed by non-contact infrared meibography followed by tear film lipid layer interferometric evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Hematoxylin-eosin (HE) staining of resected eyelid tissue revealed the absence of normal gland lobular and ductal structures at the dropout site, and noncontact infrared meibography (NIM) revealed Meibomian gland atrophy [33]. Another case report demonstrated that a two-year-old neutered female mongrel dog presented sebaceous adenitis and concurrent MGD [34]. This condition is also common in human patients.…”
Section: Pathogenesis Of Mgd In Humans and Other Mammalian Speciesmentioning
confidence: 99%
“…Hematoxylin-eosin (HE) staining of resected eyelid tissue revealed the absence of normal gland lobular and ductal structures at the dropout site, and noncontact infrared meibography (NIM) revealed Meibomian gland atrophy [33]. Another case report demonstrated that a two-year-old neutered female mongrel dog presented sebaceous adenitis and concurrent MGD [34]. This condition is also common in human patients.…”
Section: Pathogenesis Of Mgd In Humans and Other Mammalian Speciesmentioning
confidence: 99%
“…With regard to meibography, in veterinary medicine, there is not sufficient available documentation. Rabbits have been studied in main human medicine research projects [ 29 31 ], while canine studies have been conducted on meibomian gland disorder (MGD) associated with keratoconjunctivitis, ocular surface disorder (OSD) and sebaceous adenitis [ 19 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…True MGD in horses has not been previously reported, to the authors' knowledge. However, canine MGD has only recently become an active area of research, begging the consideration that this condition may also be present in the equine population 3,4,6 …”
Section: Discussionmentioning
confidence: 99%
“…5 In dogs, MGD has been implicated as a cause of ocular surface disorders. 4,6 To the authors' knowledge, true MGD has not been officially diagnosed in horses. However, other meibomian gland disorders including meibomianitis have been identified and are established causes of evaporative dry eye and granulomatous lesions.…”
mentioning
confidence: 92%
See 1 more Smart Citation